IMPLEMENTASI KEBIJAKAN PENATAUSAHAAN BARANG MILIK DAERAH - Meyzi Heriyanto, Fernanda Theodora, Febri Yuliani, (Jurnal Ilmu Administrasi Negara, 2019)
Implementation, Administration of Regional Property. This study aims to analyze theimplementation of the administration of regional property policies within the Riau ProvincialGovernment and analyze the obstacles in the implementation of policies for administering regionalproperty within the Riau Provincial Government. This study uses a descriptive qualitative researchmethod approach. Data collection techniques are interviews and observations. Key information is thegoods management official at the Riau Provincial Financial and Asset Management Agency. Secondarydata obtained from research documents. The results showed that the communication factor that occurredbetween the officials managing regional property was not good, inadequate resources both human andfinancial resources, disposition in the implementation of administration of regional property went poorly,and the bureaucratic structure in implementation was not effective. Obstacles in administering regionalproperty include incomplete goods data, lack of human and financial resources, the absence of an SOP,the Property Management Officer has not carried out his authority and responsibilities properly.